Overview of treatment success with short, long, and BPaL/M regimens in patients with drug resistant tuberculosis - Nasution, Artika Ananda Putri; Soleha, Tri Umiana; Jausal, Anisa Nuraisa; Gozali, Achmad (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Drug-resistant tuberculosis (DR-TB) remains a major challenge in global TB control efforts, particularly in middle-income countries such as Indonesia. Long-term regimens lasting 18–24 months have been associated with low treatment success rates due to their prolonged duration and high incidence of adverse drug reactions. More recent developments, namely the bedaquiline–pretomanid–linezolid regimen with or without moxifloxacin (BPaL/M), have demonstrated treatment success rates of up to 89–90% in international clinical trials. Purpose: To describe the treatment success of short-term, long-term, and BPaL/M regimens among patients with drug-resistant tuberculosis. Method: A retrospective descriptive study was conducted using medical record data of DR-TB patients who received long-term, short-term, or BPaL/M regimens during 2023–2024. Treatment outcome classification followed the WHO 2022 guidelines. The variables collected included patient characteristics, type of regimen, and treatment outcomes based on WHO standards: cured, treatment completed, treatment failed, lost to follow-up, and died. Results: Of the 148 DR-TB patients who met the inclusion criteria, 98 patients (66.2%) received long-term regimens, 17 patients (11.5%) received short-term regimens, and 33 patients (22.3%) were treated with the BPaL/M regimen. The treatment success rate (cured + treatment completed) for the short-term regimen was 76.5%, which was lower compared to the long-term regimen at 83.7%. The BPaL/M regimen demonstrated the highest treatment success rate at 87.9%. Conclusion: The treatment success rates for DR-TB patients at Dr. H. Abdul Moeloek Hospital indicate that the BPaL/M regimen provides the most favorable outcomes compared to long-term and short-term regimens. Keywords: BPaL/M Regimen; Drug-Resistant Tuberculosis; Long-Term Regimen; Short-Term Regimen; Treatment Success.